FAKTOR – FAKTOR YANG MEMPENGARUHI PENERAPAN AKUNTANSI PADA USAHA PEBISNIS DIGITAL NATIVES - Okky Savira; Indriani Indah Astuti (JURNAL ILMIAH EDUNOMIKA, 2023)
Abstract Digital natives as a generation of humans who were born and developed in the digital era will certainly not be spared from the use of technology, including in business matters. This study aims to examine the effect of perceptions about accounting, education, knowledge of accounting and knowledge of technology on the application of accounting applied to businesses with digital native backgrounds. This research was developed through an understanding of Theory of Planned Behavior. Respondents in this study were business people between the ages of 17-43 years (millennials and gen Z). The results showed that perceptions about accounting. Education and knowledge of accounting and technology knowledge influence the application of accounting applied by digital natives. Keywords : Theory of Planned Behaviour, Penerapan Akuntansi, Digital Natives